Friends of the Library Program as a Marketing Media for Library Services at LKC Binus University International: A Preliminary Research - Erika, Erika; Kangko, Danang Dwijo (Journal of Documentation and Information Science, 2017)
Libraries can make a voluntary program involving their users. The Friends of the Library Program conducted by the Library and Knowledge Center of Binus University is one example. The program allows members to get involved in the daily operations of the Library and Knowledge Center of Binus University. The program has also attracted the attention of academician and the university leaders of Binus University International. Based on this background, this study is conducted to understand the role of this program in marketing the services of the Library and Knowledge Center of Binus University International. This study is a preliminary research using a qualitative approach with exploratory method. The results reveal that this program plays a pertinent role in marketing the services of the Library and Knowledge Center of Binus University International through the members and alumni of the Friends of the Library program.